2006
DOI: 10.1016/j.physletb.2006.05.037
|View full text |Cite
|
Sign up to set email alerts
|

Gravitino overproduction in inflaton decay

Abstract: Most of the inflation models end up with non-vanishing vacuum expectation values of the inflaton fields φ in the true vacuum, which induce, in general, nonvanishing auxiliary field G φ for the inflaton potential in supergravity. We show that the presence of nonzero G φ gives rise to inflaton decay into a pair of the gravitinos and are thereby severely constrained by cosmology especially if the gravitino is unstable and its mass is in a range of O(100) GeV ∼ O(10) TeV. For several inflation models, we explicitl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
236
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 156 publications
(237 citation statements)
references
References 39 publications
(47 reference statements)
0
236
0
1
Order By: Relevance
“…So, heavier gravitinos and a lower reheating temperature as a result of a smaller decay rate of the inflaton via the gauge kinetic function, would lead to a larger branching ratio for gravitino production [15], making the problem more severe. Fortunately, gravitino production is suppressed in no-scale supergravity, and the problems mentioned above are avoided.…”
Section: Discussionmentioning
confidence: 99%
“…So, heavier gravitinos and a lower reheating temperature as a result of a smaller decay rate of the inflaton via the gauge kinetic function, would lead to a larger branching ratio for gravitino production [15], making the problem more severe. Fortunately, gravitino production is suppressed in no-scale supergravity, and the problems mentioned above are avoided.…”
Section: Discussionmentioning
confidence: 99%
“…The gravitino has a cosmological abundance determined by thermal scattering, freeze-in, and freeze-out and decay, and reaches thermal equilibrium, in accordance with (iv-A), only when it is very light. Additional sources for the gravitino production occurs in non-standard cosmological scenarios [8][9][10][11][12][13][14][15]. The gravitino abundance has been studied in detail for the case of weak-scale superpartners, for example leading to bounds on T R as a function of the gravitino mass [16].…”
Section: Jhep02(2015)094mentioning
confidence: 99%
“…Here we will provide analytic formulae which can be applied to a more generic mass spectrum of superparticles. Note that it was shown that the inflaton [26][27][28][29][30][31] as well as moduli [32][33][34][35] generically decays into a pair of gravitinos. Therefore the gravitino-dominated Universe can be realized in a broader scenario than originally assumed.…”
Section: Jhep02(2014)062mentioning
confidence: 99%
“…If the reheating temperature after inflation is high enough, the gravitino is copiously generated, and eventually dominates the Universe. In addition, the gravitino can also be produced by the inflaton decay [26][27][28][29][30][31]. In the typical mass spectra given in eq.…”
Section: Gravitino-induced Baryogenesismentioning
confidence: 99%